Gaze Behavior of Referees in Sport—A Review - Ziv, Gal; Lidor, Ronnie; Zach, Sima; Brams, Stephanie; Helsen, Werner F. (Frontiers in Sports and Active Living, 2020)
The purpose of this review was to examine the literature on gaze behavior in referees. A literature search found only 12 relevant studies. Five of those studies were conducted on referees in association football (soccer), three on judges in gymnastics, one on softball umpires, and one each on referees in team handball, rugby, and ice hockey. Seven studies reported differences in gaze behavior between referees of a higher skill level and those of a lower skill level, while four studies found no differences. In addition, five studies reported differences between referees of different skill levels in both gaze behavior and performance, while four studies found differences in performance only. A number of methodological concerns arise from the current review. Among them are the lack of studies conducted in ecologically valid conditions, the lack of studies on peripheral vision, and the lack of data on referees who are working together as teams. Based on this review, we conclude that additional research is needed to clarify the relationships between gaze behavior and performance in refereeing. Practitioners who work with referees should be cautious when adopting gaze training strategies to improve selective attention, since the data on their effectiveness are scarce and sometimes contradictory.